Dari Surau ke Madrasah: Modernisasi Pendidikan Islam di Minangkabau Abad 20 - Setiawan, Rendi; Febrian, Amara; Wigiarti, Rita (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The aim of this article is to provide knowledge about the modernization of Islamic education in Minangkabau in the 20th century. The method of this article uses literary sources in the form of books dan journals. The article result in the conclusion that modernization of Islamic education in Minangkabau in the 20th century, especially the change from the traditional education system in surau to formal education in madrasas. Surau, as an Islamic educational institution that has long been rooted in the culture of the Minangkabau people. Islamic education began to experience significant changes. Surau, as a traditional Islamic educational institution, plays an important role in forming the religious and cultural identity of the Minangkabau people. However, along with the growing influence of modernization and Dutch colonial education policies, the need for more systematic formal education began to be felt. This encouraged a change from the community-based surau education pattern to a structured madrasah with an organized curriculum, combining religious and general lessons. This modernization of Islamic education also had wider implications for the religious and social identity of the Minangkabau people in the 20th century.